Islamic Bioethics in Sri Lanka - Johansson, Andreas (Oxford Research Encyclopedia of Religion., 2024)
Sri Lankan Muslims are sometimes referred to as Moors, and they are predominantly Sunni while some Muslims are part of some smaller Shia communities such as Memons and Bhoras. Despite playing no role in the civil war in Sri Lanka fought between Tamil militant groups and the Sri Lankan government, Muslims were highly affected by the war, and there was a rise of ethnic tensions in the country following the terrorism of Zahran Hashim and the organization National Tawheed Jamaat, which killed over 250 people.